TREND ON THE LACK OF PRIVATE OPEN SPACE IN SEVERAL CONTIGUOUS HOUSING IN SIDOARJO - Christina Mediastika (Journal of Architecture&ENVIRONMENT, 2014)
Limited proportion between built area and open space of house-lots in housing district seems to become trend in some housing. Within period of occupancy, house-owners are continuously requiring more rooms. A common solution is to transform available open space in the lot into building. Several contiguous housing in Sidoarjo Regency, comprises of low-to-medium and medium-to high housing types was studied to learn on the trend. The study concluded that definition of low-to-medium and medium-to-high class housing was a correct term here. In average, respondents had duration of occupancy of 15 to 20 years and most were undertaken housing extension. From 83 respondents out of 170 suspected houses of having insufficient open space was significantly proved that the extension leaved open space toward 0%. This means that lack of private open space is a factual trend here. When lack of open space is a trend, we may easily suspect that green open space is in similar term.Interesting phenomenon was found that apart from good level of early and prior awareness on the necessity of open space, average respondents had significantly lower early knowledge on the importance of open space especially in term of providing rainwater absorption bed. Their knowledge increased gradually currently. However, their current knowledge was still lower than their awareness. This finding is expected to be useful in planning further stage of community outreach to give informal lecture among community due to actual procedure in fixing open space inexistence, especially to further generation.